Transaksi Kredit Digital (Shopee Paylater) dalam Perspektif Islam - Luluwatun Nazla; Rina Samsiyah Agustina; Alda Amalia; Lu’liyatul Mutmainah (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2023)
ShopeePayLater is a service provided by Shopee to make it easier for users to shop virtually or online in the applications they use. The research method used in this journal is qualitative research because this research describes digital credit transactions (ShopeePayLater) from the perspective of the Koran and Hadith. A qualitative approach is a research process that aims to understand the phenomenon or the object under study, so as to gain a deep understanding and find something unique. The practice of ShopeePayLater which provides services in the form of money loans using the application of a qardh or debt contract is not in accordance with the fatwa, because in practice there are several things that are not in accordance with Islamic law. Whereas in this fatwa it has been explained that the use of electronic money must be avoided from transactions that contain elements of ribawi and things that can be detrimental to both parties during a sale and purchase.